Exposure to diagnostic radiation and risk of childhood cancer: overstated risks raise unnecessary concern. Issue 6 (11th May 2011) - Hodson, Kenneth; Waugh, Jason; Nelson-Piercy, Catherine
Abstract : Commentary on: Rajaraman P Simpson J Neta G . Early life exposure to diagnostic radiation and ultrasound scans and risk of childhood cancer: case-control study . BMJ 2011 ;342 :d472 .